Multi‐Decadal Simulation of Marsh Topography Under Sea Level Rise and Episodic Sediment Loads. Issue 9 (29th August 2022) - Brand, M. W.; Buffington, K.; Rogers, J. B.; Thorne, K.; Stein, E. D.; Sanders, B. F.
Abstract: Coastal marsh within Mediterranean climate zones is exposed to episodic watershed runoff and sediment loads that occur during storm events. Simulating future marsh accretion under sea level rise calls for attention to: (a) physical processes acting over the time scale of storm events and (b) biophysical processes acting over time scales longer than storm events. Using the upper Newport Bay in Southern California as a case study, we examine the influence of event‐scale processes on simulated change in marsh topography by comparing: (a) a biophysical model that integrates with an annual time step and neglects event‐scale processes (BP‐Annual), (b) a physical model that resolves event‐scale processes but neglects biophysical interactions (P‐Event), and (c) a biophysical model that resolves event‐scale physical processes and biophysical processes at annual and longer time scales (BP‐Event). A calibrated BP‐Event model shows that large (>20‐year return period) episodic storm events are major drivers of marsh accretion, depositing up to 30 cm of sediment in one event. Greater deposition is predicted near fluvial sources and tidal channels and less on marshes further from fluvial sources and tidal channels. In contrast, the BP‐Annual model poorly resolves spatial structure in marsh accretion as a consequence of neglecting event‐scale processes. Furthermore, the P‐Event model significantly overestimates marsh accretion as a consequence of neglecting marsh surface compaction driven by annual scale biophysical processes. Differences between BP‐Event and BP‐Annual models translate up to 20 cm per century in marsh surface elevation. Plain Language Summary: Mediterranean climate zones are characterized by a long dry season and wet season marked by episodic storm systems. Marsh habitat along Mediterranean coastal zones has been dramatically reduced as a result of human development, and future prediction of marsh evolution is needed to support conservation and restoration. Here we develop a new modeling approach to investigate the role of episodic storms versus non‐storm conditions on marsh evolution. Existing biophysical models of marsh evolution poorly represent physical processes which are thought to be the most important drivers of change during storm events, and the proposed modeling approach is used to isolate the role of physical processes during storm events versus coupled biophysical processes that act slowly over non‐storm conditions. With an application of the model in Newport Bay, California, we find that sediment deposition is dominated by storms with return periods of 20 years or longer, which shape the spatial pattern of deposition. We also show the importance of compaction alongside episodic deposition for shaping the future distribution of marsh topography under sea level rise. Key Points: Large storm events (>20 year return period) are primary driver of marsh accretion in Newport Bay Spatial distribution of event‐scale deposition controlled by physical processes Biophysical accretion and compaction moderate long‐term change in marsh surface elevation